PENGGUNAAN ALAT PERAGA PAPAN POLINOMIAL UNTUK MENSTIMULASI PEMAHAMAN KONSEP MATEMATIS SISWA - Safitri , Shefira Salvabila; Darmawan, Puguh; Rofiki, Imam (Jurnal Inovasi Pembelajaran Matematika, 2024)
To increase students' understanding of mathematical concepts, manipulative teaching aids are needed to support the continuity of the learning process. This research aims to describe the use of polynomial board mathematics teaching aids, as well as determine the level of effectiveness of the polynomial board created during the learning process. The type of research used is R&D (Research and Development) research. This research method is used for product development through needs research and then development is carried out to produce tested products. Research data uses a qualitative approach through direct peer teaching trials together with media expert lecturers in the Department of Mathematics, State University of Malang. Peer teaching carried out by polynomial boards has a high level of effectiveness based on active responses when learning is carried out using models as well as input and suggestions from media expert lecturers after peer teaching activities are carried out. This teaching aid can provide students with a concrete understanding of the concept of polynomial operations, both solving contextual problems and making it easier for teachers to provide explanations regarding the concept of polynomial operations. Researchers provide suggestions, especially that manipulative media in learning is very important with the aim of deepening understanding of concepts and needing to pay attention to aspects of the relevance of the material to the teaching aids used.